Optimum conditions for sucrose production using ultrasonic treatment - Tea, Lei Kwan (2009)
The purpose of this study is to determine the optimum conditions for sucrose production using ultrasonic treatment. The raw material used in this study is coconut sugar. With the increasing number of diabetics in the world, the demands for natural, organic, non-calorific and cheap sugar are on the rise. Thus, the sucrose obtained from this coconut sugar can be used to produce fructooligosaccharides (FOS) from the reaction with fructosyl transferase (FTase) enzyme. FOS is non-digestible carbohydrates, exhibits sweetness levels between 30 to 50 per cent of sugar, low caloric value and prebiotic to stimulate the bifidobacteria growth in human colon. As such, FOS can replace the common table sugar and also artificial sweeteners that are supposedly harmful to human. Ultrasonic technology can also be promoted for the usage in the food processing industry as an alternative method to conventional heat treatment that is degradable to food quality and nutrients. The coconut sugar concentrations that were used in this study were 40, 60 and 80 % w/v, diluted in pH 5.5 acetate buffer solution. Ultrasonic frequencies of 25, 68 and 132 kHz were used to treat these coconut sugar concentrations for 5 hours with the samples being analyzed every 30 minutes. The determination of sucrose composition in the treated coconut sugar was by dinitrosalicylic acid (DNS) methods, with measurement of absorbance at 580 nm using UV-Visible Spectrophotometer. It was observed that the sucrose compositions in the coconut sugar increased with time, with occasional drops during treatment. The highest amount of sucrose was found to be in 80 % w/v coconut sugar concentration at 68 kHz ultrasonic treatment. However, the highest percentage of sucrose increased was found in 60 % w/v coconut sugar concentration. Hence, it can be concluded that the highest sucrose production was 68.63% of the original amount at conditions of 60 % w/v coconut sugar concentration and treated at 68 kHz ultrasonic treatment.